Students and mobile devices - John Traxler (Association for Learning Technology, 2010)
Many educators advocate, promote and encourage the dreams of agency, control, ownership and choice amongst students whilst educational institutions take the responsibility for provision, equity, access, participation and standards. The institutions traditionally procure, provide and control the technology for learning but now students are acquiring their own personal technologies for learning and institutions are challenged to keep pace. These allow students to produce, store, transmit and consume information, images and ideas; this potentially realises the educators' dream but for institutions is potentially a nightmare, one of loss of control and loss of the quality, consistency, uniformity and stability that delivered the dreams of equity, access and participation. This paper traces the conflicting dreams and responsibilities.